1980
DOI: 10.1139/v80-397
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of N-nitroso-N-alkyl amino acids: a facile oxidative decarboxylation

Abstract: Thispaper is dedicated to Prof. Raymond U . Lemieux on the occasion of his 60th birthday YUAN L. CHOW, DOUGLAS P. HORNING, and JOEL POLO. Can. J. Chem. 58,2477Chem. 58, (1980. Several N-alkyl or N-phenyl-N-nitroso a-amino acids were synthesized and were shown to photolytically rearrange to amidoximes with concurrent decarboxylation in solution or solid states without the presence of externally added acids. In contrast, N-nitrosonipecotinic acid, a N-nitroso p-amino acid, as well as N-nitrosopiperidine in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…5, Reaction 3) (17). Our present work suggests that the photoreaction of NPRO might trigger multiple reactions, namely, 1) NPRO may react with phosphate to create a mutagenic substance and 2) NPRO can facilitate UVA-induced release of NO to create an aminium ion and subsequent production of an alkyl-radical as well as active oxygen species that could generate 8-oxodG from dG (Fig.…”
mentioning
confidence: 75%
See 3 more Smart Citations
“…5, Reaction 3) (17). Our present work suggests that the photoreaction of NPRO might trigger multiple reactions, namely, 1) NPRO may react with phosphate to create a mutagenic substance and 2) NPRO can facilitate UVA-induced release of NO to create an aminium ion and subsequent production of an alkyl-radical as well as active oxygen species that could generate 8-oxodG from dG (Fig.…”
mentioning
confidence: 75%
“…Chow et al (17) observed that UVC-photolysis of NPRO produced piperidonoxime with the release of NO (Fig. 5, Reaction 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations